2012
DOI: 10.1186/1743-0003-9-4
|View full text |Cite
|
Sign up to set email alerts
|

A multi-center study on low-frequency rTMS combined with intensive occupational therapy for upper limb hemiparesis in post-stroke patients

Abstract: BackgroundBoth low-frequency repetitive transcranial magnetic stimulation (rTMS) and intensive occupational therapy (OT) have been recently reported to be clinically beneficial for post-stroke patients with upper limb hemiparesis. Based on these reports, we developed an inpatient combination protocol of these two modalities for the treatment of such patients. The aims of this pilot study were to confirm the safety and feasibility of the protocol in a large number of patients from different institutions, and id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
80
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(89 citation statements)
references
References 26 publications
6
80
1
2
Order By: Relevance
“…For example, many recent studies have combined high and low frequency craniocerebral magnetic stimulation and conventional localized induction therapy, [5] as well as the use of visual-motor feedback technology such as Wii, XBOX-Kinect, [32] or the recent rise of mirror therapy. [33] The effectiveness of these emerging therapies have been clinically acclaimed and a growing number of investigators have attempted to apply these findings extensively to patients with stroke at different ages and stages, with many traditional therapeutic limitations reaching a breakthrough development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, many recent studies have combined high and low frequency craniocerebral magnetic stimulation and conventional localized induction therapy, [5] as well as the use of visual-motor feedback technology such as Wii, XBOX-Kinect, [32] or the recent rise of mirror therapy. [33] The effectiveness of these emerging therapies have been clinically acclaimed and a growing number of investigators have attempted to apply these findings extensively to patients with stroke at different ages and stages, with many traditional therapeutic limitations reaching a breakthrough development.…”
Section: Discussionmentioning
confidence: 99%
“…[4] This period refers to "rapid restoration of function", commonly known as "Key rehabilitation period". Nevertheless, Kakuda et al [5] attempted to rehabilitate 204 patients with chronic stroke with a mean incidence of 5 years, using repetitive transcranial magnetic stimulation (rTMS) combined with high-frequency functional therapy. After 15 days of treatment found that upper limb movement quality and speed of execution activities are patient appears very significant improvement.…”
Section: Introductionmentioning
confidence: 99%
“…Plot showing the partial correlation between the MEP ratio and motor function tests controlling for the period after stroke onset (A-C): black circles (T1) and squares (T2), affected hand; white circles (T1) and squares (T2), unaffected hand. and chronic stroke 24,25 ) . However, the neurophysiological mechanisms underlying such functional recovery are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…In general, a greater effectiveness of NIBS in subcortical stroke patients in comparison with patients with non specified lesion site has been confirmed in a recent meta-analysis [58]. Also baseline severity of the affected upper limb significantly influenced the treatment outcome, greatest results have been observed for less impaired patients [49]. The neurochemical predictors of behavioural response to tDCS after stroke have been searched using magnetic resonance spectroscopy [70].…”
mentioning
confidence: 96%
“…This effect, in line with effects on cortical motor excitability in human [6,[44][45][46] and animal models [47], is however transitory and outlasts the stimulation period from minutes to 1 -2 hours. Multiple stimulation sessions and/ or the association of a motor training are needed to induce longer lasting effects on cortical excitability and motor function (2-4 weeks) [42,[48][49][50]. In particular, Avenanti et al (2012) evaluated the effect of 10 daily sessions of 1 Hz rTMS administered either immediately before or after physiotherapy (PT), in 30 subjects affected by chronic subcortical stroke.…”
mentioning
confidence: 99%